Geometry optimization of two-stage thermoelectric generators using simplified conjugate-gradient method. (15th March 2017) - Liu, Zhichun; Zhu, Shiping; Ge, Ya; Shan, Feng; Zeng, Lingping; Liu, Wei
Highlights: Integrating computer-aided analysis with an optimization method to design and optimize TEGs. Obtaining multi-objective and multi-parameter optimization of structure for a two-stage TEG module. Properly balancing the power output and conversion efficiency to improve them simultaneously. Abstract: Thermoelectric devices can convert thermal energy directly into electrical energy. The aim of this study was to develop an approach for integrating computer-aided analysis with an optimization method that could be applied to the design and optimization of thermoelectric generators. The optimization framework consisted of a model generator, a direct solver, and a numerical optimizer. The simplified conjugate-gradient method (SCGM) was used to build the optimizer, and the general-purpose finite-element code was used for the direct solver and model generator. This approach was applied to the multi-objective and multi-parameter optimization of geometric thermoelectric generators to design an optimal structure for both a two-stage bismuth-telluride (BiTe)-based and skutterudite-based thermoelectric generator (TEG) module. The leg length and the ratio between the cross-sectional areas (i.e., footprint) of the semiconductor columns and the TEG module were found to significantly affect the TEG performance; hence, all were incorporated into the present optimization study. Multi-objective optimization was used to realize a design that properly balanced the power output and conversion efficiency so that both improved simultaneously.